2010
DOI: 10.1590/s1517-83822010000100015
|View full text |Cite
|
Sign up to set email alerts
|

The proteolytic activity of Pseudomonas fluorescens 07A isolated from milk is not regulated by quorum sensing signals

Abstract: The proteolytic activity of Pseudomonas fluorescens 07A was investigated, and was optimal on tryptone-calcium medium. N-acyl-homoserine lactones (AHLs) were not detected on supernatants of late-exponential and stationary-phase culture broths. Synthetic AHLs or bacterial cell extracts added to the medium did not influence growth or proteolytic activity suggesting that quorum sensing might not regulate protease production in this strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…However, Pinto et al. () and Martins et al. () both found that two highly proteolytic P. fluorescens strains (07A and 041), which were isolated from raw milk, did not produce AHL molecules in any of the tested media.…”
Section: Biological Properties Of Protease Aprxmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Pinto et al. () and Martins et al. () both found that two highly proteolytic P. fluorescens strains (07A and 041), which were isolated from raw milk, did not produce AHL molecules in any of the tested media.…”
Section: Biological Properties Of Protease Aprxmentioning
confidence: 97%
“…AprX production reaches its maximum at 17.5 to 20 °C, which is lower than the optimal growth temperature of pseudomonads at around 30 °C (Figure ) (Buchon et al., ; Gügi et al., ). At the same time, a dramatic increase in AprX production or total enzymatic activity, due to booming AprX production, was observed in the late exponential or the early stationary phase, only if the cell density reached 10 7 to 10 8 cfu mL −1 in milk (Guinot‐Thomas, Al Ammoury, Le Roux, & Laurent, ; Matselis & Roussis, ; Pinto, Costa, Mantovani, & Vanetti, ; Stevenson, Rowe, Wisdom, & Kilpatrick, ). The close relation with high bacterial count indicates that induction of AprX may be a candidate for quorum sensing, a phenomenon by which bacteria can sense and respond to cell population size by means of chemical signals based on the N ‐acy homoserine lactones (AHLs) (Fuqua, Winans, & Greenberg, ).…”
Section: Biological Properties Of Protease Aprxmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, o isolado 07A apresentou maior atividade proteolítica quando comparada à P. fluorescens 041, o que também foi observado pela maior formação do halo em ágar leite, conforme relatado anteriormente. Pinto et al (2010) avaliaram a ativida de proteolítica do isolado P. fluorescens 07A usando azocaseína como substrato e a associaram com a densidade populacional. A atividade proteolítica foi detectada quando a concentração de célula foi maior que 10 8 UFC/ mL, o que indica que a produção de protease poderia estar relacionada com a densidade populacional quando as bactérias atingem a fase estacionária de multiplicação.…”
Section: Avaliação Da Atividade Proteolítica Dos Isolados De P Fluorunclassified
“…Pseudomonas fluorescens é uma importante espécie desse gênero e produz uma metaloprotease extracelular que desestabiliza a micela de caseína por hidrólise, afetando a vida de prateleira do leite UHT e a qualidade dos derivados lácteos (PINTO et al, 2010;JONGHE et al, 2011;MACHADO et al, 2013).…”
Section: Introductionunclassified